Educational process in the internet: the dialectic of knowledge and information - Emel’yanenko, Vladimir Dmitrievich; Vetoshko, Aleksandr Nikolaevich; Zolotarev, Alexei Vadimovich; Matakov, Konstantin Anatolievich; Malashenko, Irina Vladimirovna (Nuances: estudos sobre Educação, 2021)
This article explores the problem of turning information users receive on the Internet into their knowledge. The work aims to find a priority factor that ensures a higher degree of accuracy in turning information from the Internet into human knowledge. It has been shown that the nature of the World Wide Web makes it somewhat difficult to translate information coming to a person into their knowledge. It is concluded that the condition for converting information received by the user on the Internet is the person’s cognitive activity, conditioned by the development of their ideological and value sphere. If a cognizing person has sufficiently developed and stable values and attitudes, then they successfully realize themselves as a developing subject, an active participant in cognition. On the contrary, an insufficiently stable value and attitudinal sphere can lead to a passive perception of information by the individual, adaptation to reality, etc.